Clinical Applications of Iso-Inertial, Eccentric-Overload (YoYo™) Resistance Exercise - Tesch, Per A.; Fernandez-Gonzalo, Rodrigo; Lundberg, Tommy R. (Frontiers in Physiology, 2017)
In the quest for a viable non-gravity dependent method to “lift weights” in space, our laboratory introduced iso-inertial resistance (YoYoTM) exercise using spinning flywheel(s), more than 25 years ago. After being thoroughly tested in individuals subjected to various established spaceflight analogs, a multi-mode YoYoTM exercise apparatus was eventually installed on the International Space Station in 2009. The method, applicable to any muscle group, provides accommodated resistance and optimal muscle loading through the full range of motion of concentric actions, and brief episodes of eccentric overload. This exercise intervention has found terrestrial applications and shown success in enhancing sports performance and preventing injury and aiding neurological or orthopedic rehabilitation. Research has proven that this technique offers unique physiological responses not possible with other exercise hardware solutions. This paper provides a brief overview of research that has made use, and explored the efficacy, of this method in healthy sedentary or physically active individuals and populations suffering from muscle wasting, disease or injury. While the collective evidence to date suggests YoYoTM offers a potent stimulus to optimize the benefits of resistance exercise, systematic research to support clinical use of this method has only begun to emerge. Thus, we also offer perspectives on unresolved issues, unexplored applications for clinical conditions, and how this particular exercise paradigm could be implemented in future clinical research and eventually being prescribed. Fields of particular interest are those aimed at promoting muscle health by preventing injury or combating muscle wasting and neurological or metabolic dysfunction due to aging or illness, or those serving in rehabilitation following trauma and/or surgery.